Perkembangan AI (Artificial Intelligent) dalam Manajemen Operasional - Resi Juariah Susanto (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
This research was carried out in manufacturing activities where it examined the development of AI (Artificial Intelligent) in operational management processes by comparing the extent to which AI has developed in each existing manufacturer and how effective the existence of AI is. Meanwhile, AI was created to make work easier, more efficient and costs in a business cheaper. The method used is a literature study.